Lemierre's syndrome. Issue 5 (7th May 2021) - Foo, Eng Chuan; Tanti, Matthew; Cliffe, Helen; Randall, Marc
Abstract : Lemierre's syndrome is a rare and potentially life-threatening condition that follows an oropharyngeal infection, typically from Fusobacterium necrophorum, and usually affects healthy adolescents or young adults. The characteristic features are septic thrombophlebitis of the internal jugular vein and septic embolism leading to multiorgan involvement, commonly the brain, lungs and bones. We report a man with presenting symptoms suggesting hemicrania continua, whose initial imaging showed no features of dural venous sinus or jugular thrombosis. Two weeks later, he had fever, sore throat, cervical lymphadenopathy and Actinomyces meyeri grew from peripheral blood cultures. Further imaging identified thrombosis of the internal jugular vein and cerebral venous sinuses, with multifocal cavitating lung lesions. Following antibiotics and anticoagulation, he recovered without residual deficits. Lemierre's syndrome when recognised and treated early has a good prognosis but delayed treatment may result in significant morbidity or mortality.